- #1
- 85
- 0
Hi people, as you can see i am new in this forum.
Sorry if i am posting in wrong section.
Im going to try to traduce the problem.
" f(n) is the sum o n terms of a arithmetic progression. "
Show that :
f(n+3) -3f(n+2) + 3f(n+1)-f(n) = 0
I just want to know if
-3f(n+2) = f(-3n -6) ??
Sorry if i am posting in wrong section.
Im going to try to traduce the problem.
" f(n) is the sum o n terms of a arithmetic progression. "
Show that :
f(n+3) -3f(n+2) + 3f(n+1)-f(n) = 0
I just want to know if
-3f(n+2) = f(-3n -6) ??